Temporal changes in crop diversification: A case study in a Punjab village - Gagandeep Kaur; Raj Kumar (Agricultural Economics Research Review, 2023)
Punjab state is enriched with preeminent but unsymmetrical agricultural base. The significant cotton area shifted towards rice due to insect-pest attack. Besides better irrigation facilities, lower yield risk, assured marketing made rice cultivation more attractive. Diversification towards high-value crops is the need of hour to safeguard our valuable and scarce resources as rice-wheat rotation led to depletion underground water and deteriorated soil health. Therefore, there is a need to set up value addition and processing units in rural areas to enhance the profitability of alternative crops as paddy and wheat.